2021
DOI: 10.1016/j.adro.2020.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analyses for Predictors of Response to Chemoradiation in Stage III Non-Small Cell Lung Cancer

Abstract: Background Radiation with platinum-based chemotherapy is the standard of care for unresectable stage III non-small cell lung cancer (NSCLC). Despite aggressive treatment, progression-free survival and overall survival remain poor. It is unclear whether any tumor genetic mutations are associated with response to chemoradiation therapy. Methods We retrospectively reviewed clinical outcomes of patients with stage III NSCLC treated with definitive radiation who had undergon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
(51 reference statements)
1
5
0
Order By: Relevance
“…The reported efficacy of radiotherapy in the presence of DDR pathogenic variants 19,21–23 (Table 3) was supported by our data showing prolonged local PFS in radiation‐treated patients in the pDDR group. However, although Luo et al 19 showed that variants in DDR genes in patients with stage III NSCLC were associated with a good response to radiotherapy, their study was limited by the inclusion of patients who were given concurrent chemotherapy. The added value of our research is the increased sensitivity observed to radiotherapy in patients with advanced NSCLC with systemic therapy or no systemic treatment.…”
Section: Discussionsupporting
confidence: 77%
“…The reported efficacy of radiotherapy in the presence of DDR pathogenic variants 19,21–23 (Table 3) was supported by our data showing prolonged local PFS in radiation‐treated patients in the pDDR group. However, although Luo et al 19 showed that variants in DDR genes in patients with stage III NSCLC were associated with a good response to radiotherapy, their study was limited by the inclusion of patients who were given concurrent chemotherapy. The added value of our research is the increased sensitivity observed to radiotherapy in patients with advanced NSCLC with systemic therapy or no systemic treatment.…”
Section: Discussionsupporting
confidence: 77%
“…From the search results of 161 documents, 13 papers were selected for data extraction [ 4 9 , 13 19 ]. Globally, 19 clinical presentation items (CPIs) were identified.…”
Section: Resultsmentioning
confidence: 99%
“…As the DDR pathway plays a role in radiation repair, pathogenic alterations would be hypothesized to lead to radiation sensitivity. Prior studies that have found patients with DDR pathway gene alterations to have improved local-regional outcomes after radiotherapy were mostly limited to patients without subsequent ICI exposure . This suggests that the local-regional control benefit imparted by consolidative ICI treatment could minimize the difference in outcomes between patients with and without alterations in DDR genes.…”
Section: Discussionmentioning
confidence: 99%